Boiling and crystallization in three-phase two-components solution - Eliseev, V.I.; Lutsenko, V.I. (Геотехнічна механіка, 2014)
Following general laws of heat-mass exchange in multiphase systems, common tendencies of vapor bubble and crystal dynamics and growth in a solution were studied with the assumptions that the solution medium consisted of two chemically neutral components - water and sucrose –and include three phases: liquid, solid and gaseous. Conservation equations and equations for interphase interactions are formulated with taking into account specific properties of the aqueous solution of sucrose. Assumptions on which a theory of multiphase heterogeneous systems is based are presented. Dynamic behavior of the three-phase two-component medium in an axialsymmetric channel is described with the help of one-dimensional flow model. It is shown that at low sucrose concentration and initial overheating of the solution in the channelvapor bubbles increase though sugar crystals dissolve. At higher concentrations and inessential overheating, both bubbles and crystals can increase. Thus, it is possible to specify conditions under which crystallization could occurred in the solution. На основі загальних законів тепломасообміну в багатофазних системах розглянуті основні закономірності динаміки і зростання парових бульбашок і кристалів в розчині. Прийнято , що середовище складається з двох хімічно нейтральних компонентів: води і цукрози і трьох фаз: рідкої , твердої і газоподібної . Записані рівняння збереження і міжфазної взаємодії з урахуванням специфічних властивостей розчину. Вжито припущення , на яких базується теорія багатофазних гетерогенних систем . У рамках одновимірної моделі течії отримані рішення для динамічної поведінки трифазного, двохкомпонентного середовища в осесиметричному каналі. Показано , що при низьких концентраціях цукрози в каналі початковий перегрів рідини призводить до зростання парових бульбашок і до розчинення кристалів цукру. Для високих концентрацій при невеликих перегрівах можливі, як зростання бульбашок, так і зростання кристалів. Таким чином, можуть бути знайдені умови необхідні для кристалізації в розчині. На основе общих законов тепломассообмена в многофазных системах рассмотрены основные закономерности динамики и роста паровых пузырьков и кристаллов в растворе. Принято, что среда состоит из двух химически нейтральных компонентов: воды и сахарозы и трех фаз: жидкой, твердой и газообразной. Записаны уравнения сохранения и межфазного взаимодействия с учетом специфических свойств раствора. Приняты предположения, на которых базируется теория многофазных гетерогенных систем. В рамках одномерной модели течения получены решения для динамического поведения трехфазной, двухкомпонентной среды в осесимметричном канале. Показано, что при низких концентрациях сахарозы в канале начальный перегрев жидкости приводит к росту паровых пузырьков и к растворению кристаллов сахара. Для высоких концентраций при небольших перегревах возможны, как рост пузырьков, так и рост кристаллов. Таким образом, могут быть найдены условия необходимые для кристаллизации в растворе.